2007
DOI: 10.1097/ico.0b013e3180950083
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Approach to the Repeatability of the Schirmer Test Without Anesthesia

Abstract: Our study suggests that administering the ST with the patient's eyes closed produces less variable results and more repeatability than STo in normal subjects. Although our results may not extend to dry eye patient populations, we propose that STc without anesthesia can be considered by those ophthalmologists who frequently use the ST as an adjunct to the differential diagnosis of dry eye in patients presenting with ocular discomfort, making ST a more reliable test in everyday practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 12 publications
2
39
1
Order By: Relevance
“…In support of this, Singh Bhinder et al reported that the Schirmer I results change according to reflex epiphora when performed with opened eyes [30]. Indeed, closing the eyes while the test is performed has been recently found to increase its reliability, successfully minimizing the influence of such factors [31].…”
Section: Discussionmentioning
confidence: 90%
“…In support of this, Singh Bhinder et al reported that the Schirmer I results change according to reflex epiphora when performed with opened eyes [30]. Indeed, closing the eyes while the test is performed has been recently found to increase its reliability, successfully minimizing the influence of such factors [31].…”
Section: Discussionmentioning
confidence: 90%
“…2 The popularity of the ST has been attributed to its relative simplicity and low cost when compared with alternative methods of assessing tear production. 3 However, despite its widespread use, the ST has a number of shortcomings which are well recognized, [3][4][5][6][7] including poor reproducibility and poor patient comfort.…”
mentioning
confidence: 99%
“…The strip was inserted into lower temporal conjunctival sac and the wet length of the paper was measured on millimeter after 5 min. Eyes were closed during the test to get more reliable data [12]. NIBUT was performed with Tearscope Plus (Keeler Instruments Ltd., Windsor).…”
Section: Methodsmentioning
confidence: 99%